Buerger’s disease in female: rare case report - Bhoyate, Abhijit A.; Priya R., Lekshmi; Tripathi, Vidyanand; Agrawal, Piyushkumar; Moirangthem, G. S. (International Surgery Journal, 2018)
Thromboangiitis obliterans (Bureger’s disease) is a vascular disease characterized by a segmental, non-atherosclerotic inflammation of the small and medium-sized arteries and veins of the distal extremities mostly affecting young male smokers and rarely females. Only a few cases with histologic proof of the disease in females have ever been recorded in literature. We report a rare case of Buerger’s disease in a 55 years old female.